“AUTOCONTROL EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA “GENERAL JUAN LAVALLE” RIOBAMBA - CHIMBORAZO PERIODO ACADÉMICO ABRIL-AGOSTO 2019” - Huaraca Colcha, Jessica Germania (2020)
The research aimed of this work is to determine self-control in the students of the Educational Unit "General Juan Lavalle" Riobamba - Chimborazo Academic Period April- August 2019. Knowing that self-control is a vital skill for the good performance of life which allows the individual to maintain self-control and control, in terms of lack of self- control is a widespread problem that does not discriminate age, ethnicity or religion, adolescence is known as the age of out of control, it is a stage where there are significant changes regarding the control that the parents exercise. The research's approach was quantitative and a non-experimental methodology was used, for the type was descriptive, transversal, basic and field, the study population were the children of the Educational Unit "General Juan Lavalle", whose sample was not probabilistic and intentional in working with 35 students of the Tenth Year of GBD, including 18 males and 17 women; the instrument applied was the CACIA (Child and Adolescent Self-Control Questionnaire) questionnaire, which evaluated positive and negative self-control scales determining that there is a high level of self-control, which is very important for development integral of adolescents by demonstrating self-confidence, ability to relate to others, autonomy and self- confidence, is recommended to work together with the entire educational community in pisco-affective talks which promote self-control and learn skills for the purpose of improving interpersonal relationships between students.